Histidine decarboxylase knockout mice, a genetic model of Tourette syndrome, show repetitive grooming after induced fear. (19th May 2015) - Xu, Meiyu; Li, Lina; Ohtsu, Hiroshi; Pittenger, Christopher
Highlights: Hdc knockout mice have recently been validated as a genetic model of a rare genetic form of Tourette syndrome. Hdc KO mice show increased grooming, compared to HET and WT mice, after fear stress. Hdc KO mice show intact fear learning. Abstract: Tics, such as are seen in Tourette syndrome (TS), are common and can cause profound morbidity, but they are poorly understood. Tics are potentiated by psychostimulants, stress, and sleep deprivation. Mutations in the gene histidine decarboxylase ( Hdc ) have been implicated as a rare genetic cause of TS, and Hdc knockout mice have been validated as a genetic model that recapitulates phenomenological and pathophysiological aspects of the disorder. Tic-like stereotypies in this model have not been observed at baseline but emerge after acute challenge with the psychostimulantd -amphetamine. We tested the ability of an acute stressor to stimulate stereotypies in this model, using tone fear conditioning. Hdc knockout mice acquired conditioned fear normally, as manifested by freezing during the presentation of a tone 48 h after it had been paired with a shock. During the 30 min following tone presentation, knockout mice showed increased grooming. Heterozygotes exhibited normal freezing and intermediate grooming. These data validate a new paradigm for the examination of tic-like stereotypies in animals without pharmacological challenge and enhance the face validity of the Hdc knockout mouse as a pathophysiologically grounded model of tic disorders.